Indoor ventilation frequency and cognitive function among Chinese old adults: the multiple mediation effect of anxiety and self-rated health - Lu Lin; Pingping He; Sihui Qiu; Xiaohui Qiu; Jiangping Chen (BMC Geriatrics, 2025)
Abstract Background China is experiencing an increasingly serious aging population. Cognitive function is an important factor and guarantee for the quality of life of older people. Therefore, to achieve healthy aging, this study aimed to examine the sequential multiple mediating effects of indoor ventilation frequency and cognitive function on anxiety and self-rated health in the Chinese older people population. Methods Using the 2018 China Longitudinal Health and Longevity Survey (CLHLS) dataset, we finally selected 10,372 Chinese seniors over the age of 65. First, we describe the basic socio-demographic information of the sample population. Second, Spearman correlation analysis was used to determine whether there was a correlation between indoor ventilation frequency, anxiety, self-rated health, and cognitive function among Chinese older people. Finally, the SPSS macro process program was used to complete the sequence multiple mediation analysis. Results Indoor ventilation frequency, anxiety, self-rated health and cognitive function were significantly correlated (p < 0.01). Indoor ventilation frequency not only has a direct positive impact on the cognitive function of older people (effect = 0.1427; Standard error = 0.0201; 95%CI: LL = 0.1034, UL = 0.1821), but also indirectly affected cognitive function through three pathways: independent mediation of anxiety (effect = 0.0078; Standard error = 0.0021; 95%CI: LL = 0.0041, UL = 0.0121), independent mediating effect of self-rated health (effect = 0.0154; Standard error = 0.0030; 95%CI: LL = 0.0098, UL = 0.0215), and the chain mediating effect between anxiety and self-rated health (effect = 0.0046; Standard error = 0.0009; 95%CI: LL = 0.0029, UL = 0.0065). Limitations All projects are self-reported and some results may be biased. In the future, it may be more inspiring to explore more detailed and specific effects of indoor air quality on cognitive function in older people. Conclusions Studies have shown that indoor ventilation frequency can improve cognitive function by reducing anxiety and improving self-rated health in older people Chinese. Encouraging older adults to increase the frequency of indoor ventilation will benefit their mental health and cognitive function.